Genetic diversity amongst oat (Avena sativa) lines for micronutrients and agro-morphological traits - RANJAN, RAJEEV; CHAND, SUBHASH; INDU; SINGHAL, RAJESH KUMAR; RANA, MANEET; SAH, R P; GAJGHATE, RAHUL; AHMED, SHAHID; DWIVEDI, KRISHNA KUMAR (The Indian Journal of Agricultural Sciences, 2024)
The present experiment was conducted during winter (rabi) seasons of 2019–20 and 2020–21 at the ICAR-Indian Grassland and Fodder Research Institute, Jhansi, Uttar Pradesh to study the genetic diversity amongst oat (Avena sativa L.) lines for micronutrients and agro-morphological traits. For study, 150 oat accessions collected from different sources were evaluated for two years and four micronutrients (Zn, Cu, Fe and Mn) and 9 agro-morphological traits were recorded. Genotypes IG02122 (464.0 mg/kg), IG02156 (48.1 mg/kg), IG03271 (136.0 mg/kg), and IG03213 (22.0 mg/kg) had maximum Fe, Zn, Mn and Cu content in fodder (harvested at 50% flowering). Genotype IG0280 had both high Zn (36.97 mg/kg) and Mn (114.33 mg/kg); IG03233 had high Cu (18.0 mg/kg) and Mn (124.0 mg/kg); and IG02131 had high Cu (18.33 mg/kg) and Fe (369.0 mg/kg) content. Analysis of variance (ANOVA) highlighted significant genotypic differences (P<0.001) for micronutrient content and fodder yield and related traits. High heritability coupled with high genetic advance was found for micronutrients, green fodder yield, test weight, dry matter yield, plant height, tiller number and grain number suggested the preponderance of additive and fixable genetic variance for these traits. The Cu content had significant negative association with Mn content but positive with leaf length and leaf width. Principal component analysis separated the total genetic variation into five main components and covered 59.09% of the total genetic variation. Based on Mahalanobis distances, genotypes were grouped into six clusters where maximum inter-cluster distance was observed for cluster 4 and 5. Therefore, genotypes from these two clusters can be used as parents for the future breeding programmes.